Measurement of Atmospheric Volatile and Intermediate Volatility Organic Compounds: Development of a New Time-of-Flight Mass Spectrometer - Christos Kaltsonoudis; Olga Zografou; Angeliki Matrali; Elias Panagiotopoulos; Alexandros Lekkas; Mariangela Kosmopoulou; Dimitris Papanastasiou; Konstantinos Eleftheriadis; Spyros N. Pandis (Atmosphere, 2023)
A new gas inlet port combined with a novel ionization scheme have been developed and coupled to a high-resolution time-of-flight mass spectrometer (TOF MS) for the detection and measurement of atmospheric volatile (VOCs) and intermediate volatility organic compounds (IVOCs). Ions are produced predominantly by charge transfer reactions in a low-temperature plasma ionization source with minimal fragmentation. Enhanced sensitivity is accomplished by incorporating an increased-size inlet capillary in a transverse arrangement to maximize throughput in the ionization source. Additional design aspects of the new mass spectrometer enabling superior transmission include a large acceptance ion funnel and a segmented radio frequency (RF) ion guide with increased space charge storage capacity. An orthogonal TOF analyzer equipped with a two-stage reflectron and tuned to second order is employed for the determination of the mass-to-charge ratio of the ions, with a mass resolving power of >20 k at mass 500 Th. The performance of the instrument was evaluated in tests using VOC standards and in atmospheric chamber experiments to demonstrate the ability to measure a wide range of organic compounds with different functional groups. Linear signal response is demonstrated over a wide range of VOCs used in the calibration processes in the ppb range, while the instrument exhibits linear response in the ppt range as well. Detection limits as low as 1 ppt are accomplished. The potential applications of this new TOF MS instrument were demonstrated in a pilot atmospheric simulation chamber experiment.